The 253‐kb inversion and deep intronic mutations in UNC13D are present in North American patients with familial hemophagocytic lymphohistiocytosis 3. Issue 6 (28th January 2014) - Qian, Yaping; Johnson, Judith A.; Connor, Jessica A.; Valencia, C. Alexander; Barasa, Nathaniel; Schubert, Jeffery; Husami, Ammar; Kissell, Diane; Zhang, Ge; Weirauch, Matthew T.; Filipovich, Alexandra H.; Zhang, Kejian
<x xml:space="preserve">Abstract</x> Background The mutations in UNC13D are responsible for familial hemophagocytic lymphohistiocytosis (FHL) type 3. A 253‐kb inversion and two deep intronic mutations, c.118–308C > T and c.118–307G > A, in UNC13D were recently reported in European and Asian FHL3 patients. We sought to determine the prevalence of these three non‐coding mutations in North American FHL patients and evaluate the significance of examining these new mutations in genetic testing. Procedure We performed DNA sequencing of UNC13D and targeted analysis of these three mutations in 1, 709 North American patients with a suspected clinical diagnosis of hemophagocytic lymphohistiocytosis (HLH). Results The 253‐kb inversion, intronic mutations c.118–308C > T and c.118–307G > A were found in 11, 15, and 4 patients, respectively, in which the genetic basis (bi‐allelic mutations) explained 25 additional patients. Taken together with previously diagnosed FHL3 patients in our HLH patient registry, these three non‐coding mutations were found in 31.6% (25/79) of the FHL3 patients. The 253‐kb inversion, c.118–308C > T and c.118–307G > A accounted for 7.0%, 8.9%, and 1.3% of mutant alleles, respectively. Significantly, eight novel mutations in UNC13D are being reported in this study. To further evaluate the expression level of the newly reported intronic mutation c.118–307G > A, reverse transcription PCR and Western blot analysis revealed a significant reduction of both RNA and protein levels suggesting that the c.118–307G > A mutation affects transcription. Conclusions These specified non‐coding mutations were found in a significant number of North American patients and inclusion of them in mutation analysis will improve the molecular diagnosis of FHL3. Pediatr Blood Cancer 2014;61:1034–1040. © 2014 Wiley Periodicals, Inc.